Islam and the Acquisition of Knowledge (Islam dan Perolehan Ilmu) - Ashimi, Tijani Ahmad (Journal of Islam in Asia (E-ISSN 2289-8077), 2018)
Abstract Knowledge is not only learning, but it also encompasses experience. The acquisition of knowledge involves a process of training and education rather than just learning. From the early days of Islam, knowledge has been considered to be the power that is bestowed upon man in order to qualify him to be the vicegerent of Allah on earth (KhalÊfatullÉh). Without knowledge man is not strong enough to fulfill the duties and responsibilities of a vicegerent (KhalÊfah) to structure his life and his society, as it provides him with values, virtues, visions, beliefs and power. Indeed, knowledge in Islamic worldview is a unique gift from the Creator (the most Omniscience and the only Absolute God) to man. As such, it is vital for the success of man in this world and the Hereafter. Furthermore, it is undeniable fact that, knowledge is the root of man’s progress in this transitory world and a crucial factor in his well-being after his demise. Based on the above facts, this humble paper aims to explore vis-a-vis the importance of knowledge acquisition in the view of Islam and to disclose the serious attention that Islam has paid toward acquisition of knowledge. However, to achieve the aims and the objectives of this paper, revelation based approach is applied, that is by referring to the Holy Scripture of Islam (holy Qur’an) and its perception on knowledge. Finally, the paper provides a brief conclusion and some recommendations. Keywords: Knowledge, Islam, Qur’an, Sunnah, Muslim, Social sciences, Natural sciences. Abstrak Ilmu pengetahuan bukan sahaja berkaitan pembelajaran, tetapi juga merangkumi pengalaman. Ilmu pengetahuan didapati melalui proses latihan dan pendidikan tidak hanya proses pembelajaran secara rasmi. Sejak bermulanya Islam, ilmu pengtahuan telah dianggap sebagai satu anugerah yang telah diberikan kepada manusia untuk melayakkannya menjadi khalifah di muka bumi ini. Tanpa ilmu pengetahuan manusia tidak berupaya untuk memikul tugas dan tanggungjawab sebagai seorang khalifah dalam mengatur kehidupannya dan masyarakat, ini kerana ia memberi nilai-nilai murni, sifat-sifat kebaikan, aspek kepercayaan dan kekuasaan. Sesungguhnya ilmu pengetahuan menurut perspektif Islam adalah anugerah yang unik yang diberikan oleh Pencipta (Yang Maha Mengetahui dan Maha Esa) kepada manusia. Ia merupakan syarat penting dan faktor utama bagi kejayaan manusia di dunia dan akhirat. Berdasarkan fakta yang disebutkan, kertas ini meneroka perihal pentingnya mencari ilmu pengetahuan menurut pandangan Islam dan memberi penekanan pada perkara-perkara penting dalam usaha mendapatkannya. Walau bagaimanapun, untuk mencapai matlamat dan objektif kertas ini, pendekatan berasaskan wahyu diterapkan, iaitu dengan merujuk kepada Kitab Suci Al-Quran (suci Al-Quran) dan persepsinya terhadap ilmu pegetahuan. Kertas ini akhirnya membuat kesimpulan ringkas dan juga memberi beberapa cadangan dan saranan. Kata Kunci: Ilmu pengetahuan, Islam, Quran, sunnah, orang Islam, Sains sosial, Ilmu alam.